Specific instruments to evaluate their knowledge of asthma: a systematic review - Cristian Roncada (Medicina, 2015)
Introduction: The evaluation of the level of asthma knowledge is one of the major outcomes for studies related to educational programs on asthma. Hence, identifying the particular instrument suitable for this outcome is essential to the success of studies in this field. Objective: To identify specific instruments to assess knowledge of asthma, analyzing the main characteristics and quality criteria for psychometric validation. Methods: A systematic review was performed to identify outcome measures available to assess knowledge of asthma in children, adolescents, guardians and caregivers. We applied the logic of search in Medline, Lilacs, Scopus, DirectScience, PsycINFO, Cochrane and Tripdatabase. Articles were included by description of the development and psychometric testing of the questionnaires on asthma knowledge. Quality criteria for content validity, construct validity, internal consistency and reproducibility were evaluated and assigned as “positive”, “intermediate” or “negative” rating. Results: Twenty-two instruments were included in the study. None of them had a positive review for all four evaluated psychometric properties. Six received positive or intermediate classification, one of these was developed in Portuguese-BR. Conclusion: Currently, there are 22 questionnaires available to assess the level of asthma knowledge, but most of the instruments do not have full psychometric validation